High-Frequency Repetitive Transcranial Magnetic Stimulation Applied to the Parietal Cortex for Low-Functioning Children With Autism Spectrum Disorder: A Case Series - Yang, Yingxue; Wang, Hongxing; Xue, Qing; Huang, Zhaoyang; Wang, Yuping (Frontiers in Psychiatry, 2019)
Background: Repetitive transcranial magnetic stimulation (rTMS) is a safe and efficacious technique to stimulate specific areas of cortical dysfunction in several neuropsychiatric diseases; however, it is not known whether high-frequency rTMS (HF-rTMS) over the left inferior parietal lobule, in low functioning children with autism spectrum disorder (ASD), improves core symptoms. Method: Eleven low-functioning children with ASD completed two separate HF-rTMS treatment courses, 6 weeks apart. Each treatment course involved five 5s trains at 20 Hz, with 10-minute inter-train intervals, on left inferior parietal lobule each consecutive weekday for a 3-week period (15 treatments per course). Participants were assessed at five time points: immediately before and after the first HF-rTMS course, immediately before and after the second HF-rTMS course, and 6 weeks after the second rTMS treatment course. Treatment effectiveness was evaluated using the Verbal Behavior Assessment Scale (VerBAS) and Autism Treatment Evaluation Checklist (ATEC). The latter test consists of four subtest scales: Language, Sociability, Sensory, and Behavior. In addition, daily treatment logbooks completed by parents were considered as one of the outcome measures. Results: Participants showed a significant reduction in language and social related symptoms measured by ATEC from pre-treatment to the 6-week follow-up after the second treatment course. Moreover, some possible improvements in imitation and cognition were reported by caregivers. Conclusions: Our findings suggest that HF-rTMS over the left parietal cortex might improve core deficits in low-functioning children with ASD.